Quality Assessment of English Learning in Junior High School Using the Online Photo Essay Assignment Method - Vica Ananta Kusuma; Binti Muflikah; Sari Famularsih (IJORER : International Journal of Recent Educational Research, 2023)
Development in information technology, especially the internet and social media today, opens up opportunities for education practitioners (lecturers/teachers) to innovate in improving the quality of learning for their students. It is done to look up the conventional learning methods as investigated in this study, that is, the assessment of the quality of learning using the online photo essay assignment method. This type of research is quantitative by taking samples in two classes at the Junior High School in English. Primary data is obtained from calculating the percentage of answers to surveys given to students, as well as assessments from teachers on the results of online photo essay uploads conducted by students. This research aims to provide alternative learning methods adapted to the development of information technology so that the learning process is expected to be more exciting and can impact optimal learning outcomes. The result showed that the student assignment method in the form of online photo essays positively contributed to the quality of English learning by reviewing the process, media, and results aspects.